PATTERNS OF ONLINE MEDIA COMMUNICATION IN NEWS COVERAGE ON OKEMEDAN.COM - Akbar Aldi Kautsar; Anang Anas Azhar; Erwan Efendi (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2022)
The goal of this study is to describe the communication patterns of okemedan.com online media journalists when covering news, as well as the communication barriers they face when doing so. This research method employs qualitative research with a descriptive qualitative research approach, with primary data collected through observation instruments, interviews, field notes, and documents, and secondary data collected through graphic documents. Domain analysis is a data analysis technique. Triangulation is a technique for determining the validity of data. The study's findings show that (1) journalists use a two-way communication pattern during interviews with resource persons, then say hello to the resource person, and communicate politely and politely. Before the interview, introduce yourself and ask the interviewee ethical questions. (2) Communication barriers with resource persons include resource persons who are unwilling to be interviewed, resource persons who are closed, resource persons who are difficult to find and contact, and resource persons who do not understand the essence of questions posed by journalists.